From signaling pathways to clinical trials: mesenchymal stem cells as multimodal regenerative architects in liver cirrhosis therapy - Vida Bozorgi; Mahnaz Babaahmadi; Mohammad Salehi; Jamshid Vafaeimanesh; Ensiyeh Hajizadeh-Saffar (Stem Cell Research & Therapy)
Abstract Liver cirrhosis, a chronic disease distinguished by extensive scarring in the liver, results in liver dysfunction and fatal complications such as portal hypertension and liver cancer. Although early interventions can retard or reverse early injury, advanced stages often call for liver transplantation—a therapy undermined by donor shortage and logistical setbacks. Emerging cell therapies, particularly those based on mesenchymal stem cells (MSCs), offer a novel approach to addressing these clinical needs. MSCs, self-renewing multipotent stromal cells, can differentiate into many cell types, including hepatocyte-like cells. Immune regulation, regenerative signaling, and anti-scarring effects are three mechanisms that underlie their therapeutic promise. MSCs modulate immune cells, suppressing inflammation and promoting tissue healing. MSCs release several growth factors and cytokines, including hepatocyte growth factor (HGF), vascular endothelial growth factor (VEGF), epidermal growth factor (EGF), and matrix metalloproteinases (MMPs), which participate in tissue regeneration. Among these, HGF is bivalent, as it supports hepatocyte proliferation while also inhibiting fibrosis and apoptosis, thereby allowing the tissue to repair and protect itself. Recent advances identify extracellular vesicles from MSCs (MSC-EVs) as a cell-free alternative. The vesicles contain bioactive cargo, including microRNAs and proteins, that regulate immune function, inhibit cell death, and facilitate liver repair. Preclinical models of cirrhosis in animals have demonstrated MSC-EVs to enhance liver function, reduce scarring, and improve survival. This review integrates current knowledge of MSC-based therapies, their mechanisms, clinical potential, and challenges associated with their deployment. More than 50 clinical trials are registered or planned to evaluate MSC-based treatments for liver cirrhosis. Preclinical and clinical outcomes are encouraging; however, further work is needed to optimize delivery strategies, confirm safety, and facilitate the universal clinical use of this approach. Advances in MSC-guided regenerative medicine have the potential to revolutionize therapy for end-stage liver disease, offering hope where traditional treatments fail.